Differences in Healing of a Horizontal Root Fracture as Seen on Conventional Periapical Radiography and Cone-Beam Computed Tomography - Ronnachat Rothom; Patchanee Chuveera (Hindawi Limited, 2017)
Different locations and healing patterns of horizontal root fractures bear different prognoses. Conventional periapical radiographs have been routinely used for the evaluation of the locations and healing of horizontal root fractures, with the limitation of presenting two-dimensional images. The three-dimensional imaging technology, cone-beam computed tomography (CBCT), has recently gained interest in dental traumatology, in particular for locating and diagnosing root fractures. However, the assessment of healing patterns of horizontal root fracture using CBCT compared to conventional radiographs has not been established. This case report describes the different healing patterns evaluated by two-dimensional radiographs and CBCT of a horizontally root-fractured maxillary right central incisor treated with mineral trioxide aggregate (MTA) with a two-year follow-up. The findings suggest that the healing patterns of horizontal root fractures seen on conventional radiographs and CBCT may be different.